(untitled) (Revista Inclusiones, 2020)
The article is devoted to the improvement of approaches to the formation of the overall strategic potential of an enterprise. It has been established that if all conditions are provided to ensure the transition to the next stage, a company continues to develop at a consistently high rate and receives such an important resource in the competitive struggle as time, which is also a competitive advantage. It has been proved that if all processes in an enterprise proceed at a consistently high level and sufficient conditions for the cumulative effect to occur are fully formed at each previous level, the development crisis is characterized by a positive value. It has been revealed that each level of the development system of the overall strategic potential reflects the level of strategy in the system of development strategies and each element of the system determines the development goal at the corresponding level.